Efektivitas Konseling Kelompok Realita Untuk Meningkatkan Resiliensi Siswa SMP Islam Al Amal (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This study aims to determine the effectiveness of reality approach group counseling to improve students' resilience attitudes of Al Amal Islamic Junior High School Surabaya. This research uses quantitative research. This type of research uses the Pre-Experiment One Group Pre-Test and Post-Test Design. The population in this study were the 8th grade students of Islamic Junior High School Al Amal Surabaya, totaling 53 students, from that population the research sample was taken 5 students using purposive sampling. The instrument in this study used two instruments, namely the data collection instrument consisting of a questionnaire and self-reflection journal, and a treatment material instrument developed specifically by the researcher. Data analysis in this study using Paired Sample t-Test, is a type of statistical test that aims to compare the mean of two paired groups. The results of this study indicate that the significance level of the t-test results is 0.067, so it can be concluded that the reality approach group counseling is not significant in increasing the resilience attitude of students of Al Amal Islamic Junior High School